Clinical and radiographic findings that impact treatment: a study of 418 proximal humerus fractures - Julian Forero-Millan; Wondwossen T. Lerebo; Vandan S. Patel; Lewis Fanney; Alexandre Arkader; Jie C. Nguyen (Emergency Radiology, 2026)
Abstract Purpose Regional skeletal maturation can influence injury pattern and treatment selection. This study aimed to systematically characterize pediatric proximal humerus fractures to identify radiographic findings that impact treatment selection. Methods This IRB-approved retrospective comparative study included pediatric patients (< 18 years), who underwent pre-treatment radiographic examination for proximal humerus fractures (2014–2024). Demographics, injury mechanism, skeletal maturity, physeal involvement and pattern, maximum displacement, angulation, and treatment were collected. Findings between surgically and non-surgically treated fractures were compared using descriptive statistics and using optimal cutoff values, determined using the receiver operating characteristic (ROC) analysis and the Youden index, with additional regression modeling to identify independent predictors of surgery. Results This study of 418 children (mean age, 9.8 ± 3.6 years; 53.1% girls, 46.9% boys) included fractures in 90.0% skeletally immature, 8.9% maturing, and 1.2% mature humeri. A minority had physeal involvement (14.0%) and underwent surgical treatment (10.0%). Overall, median fracture displacement (relative to shaft width) was 24% (IQR, 12%–53%) and angulation was 14° (IQR, 8–23°) with optimal thresholds identified at > 42% and > 22°, respectively. In the adjusted multivariable logistic regression, independent predictors for surgery included fracture displacement > 42% (OR: 13.3, 95% CI: 4.2–41.7, P < 0.01), age > 12 years (OR: 7.2, 95% CI: 2.2–24.1, P < 0.01), and a non-fall injury mechanism (OR: 6.3, 95% CI: 2.4–16.7, P < 0.01). Conclusion In our study group, fracture displacement, together with older age and a non-fall injury mechanism, independently impacts management of pediatric patients with acute proximal humerus fractures.